Llorca Abad, G, Prósper Ribes, J. y Vacas Gómez, M. M. (2023). Anatomía de una serie: sobre cómo realizar y producir una ficción audiovisual - García de Torres , Elvira (2023)
The book "Anatomy of a serie: on how to make and produce audiovisual fiction" addresses, as José Luis Moreno Maicas very correctly indicates in the prologue, this element of popular culture. A phenomenon, that of series, that has a great impact on our way of understanding the world, with fewer and fewer limitations. Nowadays, directors, audiovisual creators, societies and fictions, previously located on the margins of the mainstream or with little impact on the local market such as The Squid Game or The Paper House, obtain unexpected audience shares and contribute to accelerating socialization in the global village. We are, the authors state at the beginning of the work, in the golden age of fiction series.